Pengaruh Karakteristik Individu dan Kompetensi Kerja terhadap Pengembangan Karir Karyawan PT Financial Agency - Mila Asmawiani Okta; Elcy Handayani Pramita (MAMEN: Jurnal Manajemen, 2025)
This study aims to examine and analyze the effect of individual characteristics and work competencies on the career development of employees at PT Financial Agency. The population and sample consist of 35 employees, and the sampling technique used is a census, meaning all employees were included as respondents. Data were collected through questionnaires, interviews, and documentation studies to ensure comprehensive and reliable information. The data analysis was conducted using multiple linear regression to assess the influence of both variables either partially or simultaneously on career development. The results indicate that individually, individual characteristics have a positive and significant impact on employee career development. This suggests that personal traits such as motivation, personality, and attitude play an important role in career advancement. Furthermore, work competencies also showed a positive and significant effect on career development when assessed independently. This reflects the importance of technical skills and abilities in supporting career growth. Simultaneously, both individual characteristics and work competencies have a positive and significant influence on career development, highlighting the crucial role these factors play in shaping career strategies at PT Financial Agency.